Leveling the playing field? A qualitative and quantitative examination of the EU directive on public country-by-country reporting - Hannah Gundert; Christoph Spengel; Stefan Weck (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The recent enactment of Directive 2021/2101 by the EU introduces a public Country-by-Country Reporting (CbCR) regime, with the aim of promoting a level playing field for businesses operating within the EU Single Market. The directive seeks to bolster tax transparency requirements for multinational enterprises (MNEs), with the objective of reducing disparities in international tax planning potential when compared to smaller, domestic firms. However, the efficacy of public CbCR in achieving this objective hinges on equitable treatment of MNEs, irrespective of their geographical location. In this study, we examine whether the public CbCR Directive introduces unintended disparities between (1) MNEs domiciled in different EU member states and (2) MNEs domiciled within and outside of the EU. Employing an expert survey, we assess the national implementation of the directive across member states, revealing significant variations, particularly concerning the deferment of sensitive information disclosure and permitted data sources. Subsequently, conducting a descriptive analysis of firm-level financial and ownership data, we analyze the differential impact on MNEs domiciled within versus outside the EU. Our findings indicate that the directive predominantly affects MNEs headquartered in the EU, with these entities disclosing, on average, a significantly higher proportion of their global operations on a disaggregated, country-by-country basis. We conclude that the current form and implementation of the directive likely introduces unintended disparities, contrary to the intended goal of establishing a level playing field, and suggest stronger guidance and fewer transposition options.
Keywords: F23; G38; H26; M41; 330; tax transparency; tax disclosure; country-by-country reporting; European Union